Looking to belong: first- and second-generation Latino students at Purdue University, Indiana - Veiman Echeverría, Marilyn (2018)
Latino students, immigrants whether first or second generation, who have been raised in local excluded communities such as enclaves, find that integrating into the university community is a transition that goes beyond the academic challenge. Their cultural background and socioeconomic position differentiate them in a predominantly Caucasian middle-class sociocultural context. Studies show that attaining a sense of belonging to the university community is key to academic achievement and persistence, while the lack of this experience is associated with a statistically high Latino college desertion. Acknowledging that the lack of a sense of community on campus is a cause for desertion, researchers analyze here some of the elements that produce the experience of a sense of community in Latino students at Purdue University in Indiana, USA. Two instruments were applied to the interest group of volunteers: in-depth interviews to explore indicators such as community of origin, language used at home, and perception of college inclusion or exclusion, and a quantitative survey to analyze the “sense of belonging”. Results were combined with the grade point average in search for associations with academic persistence.